(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Vestibular stimulation was reported to inhibit the stress axes and release stress in healthy young adults. However, the stimulation delivered must be comfortable or ideal to attain the maximum beneficial effects. Aims and objectives: The present study aimed to assess the psychological, biochemical, and immunological parameters immediately after vestibular exercises in healthy young adults. Materials and methods: A total of fifty undergraduate medical students were part of the study after obtaining written informed consent. Vestibular stimulation was administered using electrical vestibular nerve stimulation. Depression, anxiety, and stress were assessed using the DASS 21 questionnaire. Salivary cortisol and IgA levels were measured using Elisa kits. Results: The mean age of the participants is 19±0.42 years and mean weight is 62±2.55kg and the mean height is 164±6.79 cm. There was a significant decrease in depression scores followed by immediate vestibular stimulation. There was a significant decrease in anxiety scores followed by immediate vestibular stimulation. There was a significant decrease in stress scores followed by immediate vestibular stimulation. There was a significant decrease in salivary cortisol followed by immediate vestibular stimulation. No significant difference was observed in the salivary IgA levels. Conclusion: The study results in support that electrical vestibular nerve stimulation was beneficial as there is a decline in depression, anxiety, and stress scores and also a decline in cortisol levels. The IgA levels were slightly decreased but not statistically significant.